QARAQALPAQ XALÍQ QOSÍQLARÍNDA «BAWÍR» KONCEPTINIŃ LINGVOMÁDENIY ANALIZI - Qayıpnazarova, U. (SCIENCE and SOCIETY, 2025)
The article examines the concepts of "liver" in the spoons of the Karakalpak people, reveals somatic phraseology and somatisms in the customs of the Karakalpak people.
Keywords: somatism; phraseological unit; concept; tradition